Representation of Indonesia in the 2015 Southeast Asia’s Haze in the Guardian And the New York Times - Shara Monarizka (Passage, 2017)
In 2015 Indonesia was held responsible for an environmental problem caused by the haze resulting from forest fires that spread across several neighbouring countries. The present research aims to examine the representation of Indonesia in the Guardian and the New York Times regarding the 2015 Southeast Asia’s haze and to uncover ideology underlying such a representation. This study employs the qualitative method and the sociocognitive approach to Critical Discourse Analysis to conduct the semantic macrostructures analysis and interpret the results. The data used in the research include six articles from the Guardian and three articles from the New York Times. The results reveal that Indonesia is mostly represented negatively in both Western newspapers. The dominant ideology behind the representations in both newspapers is capitalism.Keyword: Representation, critical discourse analysis, news articles, Western newspapers, the 2015 Southeast Asia’s haze